Import tax compliance: a study of customs agents in Malaysia utilising the theory of planned behaviour - Mohamed, Mirza Bin (2016)
Unlike tax accountants and advisors within direct tax, Customs law in many countries requires importers to employ licensed Customs agents. This study extends the tax literature by examining the role of Customs agents in import tax compliance. In Malaysia, as an example of a country where Customs are responsible for about one-third (MYR30 billion on average between 2005 to 2014) of total government revenue collections, the function of Customs agents is to: assist importers in meeting their import tax liabilities; prepare and submit all necessary import documentation to Customs; as well as collect and pay all revenue to the Customs administration. Customs agents are bound by the Customs Act 1967 and are required to pass a public exam before becoming formally qualified and licensed Customs agents.